KEKAYAAN JENIS TUMBUHAN LIANA DI KAWASAN TAMAN HUTAN RAYA RADEN SOERJO SUB WILAYAH MOJOKERTO - Yulia Dwi Puspita; Pujiastuti Pujiastuti; Imam Mudakir (FKIP Universitas Jember, 2016)
Raden Soerjo Gran Forest Park is a conservation area or called a conservation forest that used to collect plants and animals. The plants and the animals in there used as a research material by experts and students. This research was conducted in Raden Soerjo Gran Forest Park Sub Mojokerto Region, precisely at along the road to the Watu Ondo Waterfall. One of the species plants that exist in there is Liana. Liana is a species plant that requires other higher plants to get sunlight to growth. Liana is an important and distinctive component of tropical forests. The purpose of this research is to know the diversity of liana species in Raden Soerjo Gran Forest Park. Data retrieval is done by using explored method. The results of this research have been found 24 species of plants belong to 15 families, which is Piperaceae, Rubiaceae, Rosaceae, Moraceae, Smilacaceae, Arecaceae, Vitaceae, Fabaceae, Araceae, Apocynaceae, Menispermaceae, Elaeagnaceae, Urticaceae, Convolvulaceae, and Commelinaceae.